Pengembangan Wirausaha Marning Jagung Nuzea Terhadap Keahlian Berwirausaha Santri Pondok Pesantren Tarbiyah Islamiyah Desa Cinyawang Kecamatan Patimuan - Sudrajat, Bayu; Fany Permana, Aji; Firmansyah, Ichsan; Wati, Catur Ira (Jeksyah: Islamic Economics Journal, 2022)
Islamic boarding school is one of the Islamic education in Indonesia. Reform and reconstruction of Islamic education and its institutions need to be carried out, especially observing the development of the global world which requires every Islamic educational institution to continue to improve itself if it does not want to be abandoned by its devotees. There are still or not a few public perceptions that say that students have an image that is not positive enough in the entrepreneurial world. Another problem faced is the fate of the santri after 'study' from the Islamic boarding school. Employment opportunities for them are very small, especially if they do not have a general education provision. This research is a field research using a qualitative approach. The data in this study are primary data obtained from the Tarbiyah Islamic Boarding School and secondary data in the form of books that support this research. Methods of data collection using observation, interviews and documentation. The results showed that the Tarbiyah Islamiyah Islamic Boarding School in Cinyawang Village, Patimuan District, applied entrepreneurship to its students. Without eliminating its main characteristics as a boarding school, namely expertise in the field of religion. With this entrepreneurship, it encourages an economic independence in the Tarbiyah Islamic Boarding School environment. The impact in the development of entrepreneurship is not only felt by the students. But it also has an impact on the economy of Islamic boarding schools, alumni of students and also the surrounding community.